Apa Yang Mempengaruhi Penghindaran Pajak Di Perusahaan Sektor Kesehatan? - Nusron, Lulu Amalia; Nugraheni, Dinamipa; Pramudiati, Ningrum (Akuisisi : Jurnal Akuntansi, 2024)
Health sector companies during the Covid-19 pandemic experienced a significant increase in profit. The researcher wants to know whether companies with high profits tend to avoid taxes through company size, company age, leverage, and profitability. The companies studied were those listed on the Indonesia Stock Exchange in 2015-2021 using the purposive sampling method resulting in a total sample of 8 companies. This research is a type of quantitative research using secondary data obtained from the financial reports of a sample of companies that have been determined. The data analysis technique used is multiple linear regression analysis. The research results show that the variables company size, company age, and leverage have an effect on tax avoidance. Meanwhile, the profitability variable has no effect on tax avoidance